Use of Fermented Cocoa Skin as Raw Material for Carp Feed (Cyprinus carpio): Use of Fermented Cocoa Skin as Raw Material for Carp Feed (Cyprinus carpio) - Mustaqim Mustaqim (SEAS (Sustainable Environment Agricultural Science), 2022)
This study aimed to determine the use of fermented cocoa pods to see the growth rate of feed conversion and survival of carp (Cyiprinus carpio). This research was carried out at the Laboratory of the Faculty of Agricultural and Animal Sciences, Universitas Islam Kebangsaan Indonesia using a completely randomized design or (CRD) 4 treatments with 3 replications consisting of A: control, B: 35% fermented cocoa husk + 65% commercial pellet feed, C: 40% fermented cocoa husk + 60% commercial pellet feed, D: 45% fermented cocoa husk + 55% commercial pellet feed. The results showed that the addition of fermented cocoa skin into pellet feed had a significant effect on growth in length, weight, and feed conversion of carp (Cyiprinus carpio) and significantly affected survival where F count > F table.